Developing a rapid evidence response to COVID‐19: The collaborative approach of Saskatchewan, Canada. Issue 1 (22nd June 2021) - Groot, Gary; Baer, Susan; Badea, Andreea; Dalidowicz, Michelle; Yasinian, Maryam; Ali, Anum; Carr, Tracey; Reeder, Bruce; ,
Abstract: Introduction: The COVID‐19 Evidence Support Team (CEST) was a provincial initiative that combined the support of policymakers, researchers, and clinical practitioners to initiate a new learning health cycle (LHS) in response to the pandemic. The primary aim of CEST was to produce and sustain the best available COVID‐19 evidence to facilitate decision‐making in Saskatchewan, Canada. To achieve this objective, four provincial organizations partnered to establish a single, data‐driven system. Methods: The CEST partnership was driven by COVID‐19 questions from Emergency Operational Committee (EOC) of the Saskatchewan Health Authority. CEST included three processes: (a) clarifying the nature and priority of COVID‐19 policy and clinical questions; (b) providing Rapid Reviews (RRR) and Evidence Search Reports (ESR); and (c) seeking the requestors' evaluation of the product. A web‐based repository, including a dashboard and database, was designed to house ESRs and RRRs and offered a common platform for clinicians, academics, leaders, and policymakers to find COVID‐19 evidence. Results: In CEST's first year, 114 clinical and policy questions have been posed resulting in 135 ESRs and 108 RRRs. While most questions (41.3%) originated with the EOC, several other teams were assembled to address a myriad of questions related to areas such as long‐term care, public health and prevention, infectious diseases, personal protective equipment, vulnerable populations, and Indigenous health. Initial challenges were mobilization of diverse partners and teams, remote work, lack of public access, and quality of emerging COVID‐19 literature. Current challenges indicate the need for institutional commitment for CEST sustainability. Despite these challenges, the CEST provided the Saskatchewan LHS with a template for successful collaboration. Conclusions: The urgency of COVID‐19 pandemic and the implementation of the CEST served to catalyze collaboration between different levels of a Saskatchewan LHS.